The Impact of Foreign Acquisitions on the Investors' R&D Activities – Firm-level Evidence - Joel Stiebale (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper provides empirical evidence on the relationship between cross-border acquisitions and innovation activities at the firm level. In contrast to previous studies that analyze the effects on innovation in target firms, this paper investigates the effects on the investing firms. For the empirical analysis a unique firm-level data set is constructed that combines survey data for German firms with a merger and acquisition database. After a cross-border acquisition, investing firms display a higher rate of domestic expenditures for research and development. After controlling for endogeneity of foreign acquisitions by estimating a two-equation system with limited dependent variables and applying instrument variable techniques it is found that part of this correlation stems from a causal effect. The estimated effects are robust towards alternative identification strategies and are higher in industries with high knowledge intensity. The analysis is complemented by an investigation of the effects on tangible investment spending and by a comparison of the effects of cross-border acquisitions to those of Greenfield foreign direct investments and domestic M&As.
Keywords: D21; F23; G34; C31; O31; O33; 330; Multinational enterprises; mergers and acquisitions; innovation; Multinationales Unternehmen; Übernahme; Direktinvestition; Innovation; Industrielle Forschung; Schätzung; Deutschland